Analisis Framing Pembentukan Citra Soemarmo Hadi Saputro Menjelang Pemilihan Walikota Semarang Tahun 2015 di Media Harian Rakyat Jateng - Adhitama, Airlangga Pradipta (Universitas Semarang, 2016)
Soemarmo Hadi Saputro elections in Semarang in 2015 that was held in December to invite the attention of the mass media. How the People's Daily Java Soemarmo image framing events in the news ahead of Election 2015. This study aims to determine how the media in reporting the People's Daily Java Soemarmo as a candidate for mayor using the structure of syntax, script, thematic and rhetorical. This study used a qualitative descriptive, framing analysis techniques with models developed by Pan and Gerald Zhongdhang M.Kosicki. The results of analysis of this study is the People's Daily Java-related news framing Soemarmo as a candidate for mayor of Semarang to prioritize the elements of persona and the elements of what. Although the news framing Soemarmo forward the elements of who and what, the People's Daily Java still show neutrality and objectivity in reporting to display items of news by displaying completeness 5W + 1H.